2018
DOI: 10.24106/kefdergi.2140
|View full text |Cite
|
Sign up to set email alerts
|

İlkokul Öğretmenlerinin Bitişik Eğik Yazı ve Dik Temel Harflerin Kullanımına İlişkin Görüşlerinin Değerlendirilmesi

Abstract: Bu araştırmanın amacı, ilkokul öğretmenlerinin okuma-yazma eğitimi sürecinde bitişik eğik yazı ve dik temel harflerin kullanımına ilişkin görüşlerini ortaya koymaktır. Bu araştırmada nitel araştırma yöntemlerinden olan olgubilim kullanılmıştır. Çalışma grubunu 2016-2017 eğitim öğretim yılında ülkemizin çeşitli bölgelerinde görev yapmakta olan 85 ilkokul öğretmeni oluşturmaktadır. Araştırmada veri toplama aracı olarak açık uçlu sorulardan oluşan yarıyapılandırılmış görüşme formu kullanılmıştır. Görüşme formunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
1
6
0
1
Order By: Relevance
“…This study provides detailed knowledge about the preferences of children with special needs regarding on digital games. When the literature was examined, many studies on children with typical development and their parents were found (Eryol, 2023;Ferguson, 2015;İnce, 2022;Jones, 2014;Lemmens et al, 2011;Mercan-Uzun et al, 2023;Smith, 2010;Sönmez & Sönmez, 2023;Swing et al, 2010;Toran et al, 2016;Üstündağ, 2019). However, studies investigating the effects of digital games on children with special needs are quite limited.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This study provides detailed knowledge about the preferences of children with special needs regarding on digital games. When the literature was examined, many studies on children with typical development and their parents were found (Eryol, 2023;Ferguson, 2015;İnce, 2022;Jones, 2014;Lemmens et al, 2011;Mercan-Uzun et al, 2023;Smith, 2010;Sönmez & Sönmez, 2023;Swing et al, 2010;Toran et al, 2016;Üstündağ, 2019). However, studies investigating the effects of digital games on children with special needs are quite limited.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…According to research done in Turkey, primary school teachers do not feel that they are at a suitable level of professional competence or ability to teach kids this skill. It is advised that entrepreneurial courses be taught through undergraduate and graduate education programs (Akyürek & Şahin, 2013;Berk, 2009) in order to improve this competence in faculties of education. 21.…”
Section: Discussionmentioning
confidence: 99%
“…Parents are perceived as intermediaries in their children's interaction with digital technologies (Plowman et al, 2012). Children are drawn to utilising digital tools as a result of seeing people using them in their daily lives (Toran et al, 2016). This is understandable because children are skilled observers.…”
Section: Theoretical Frameworkepígrafementioning
confidence: 99%